A Detail Review on Heart-Leaved Moonseed (Tinospora cordifolia) Medicinal Plant - Vinotha Sanmugarajah; Gowri Rajkumar; P.A.H.R. Panambara (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2022)
Worldwide, a usage of herbal medicine is gradually increasing for the safety and maintains the health due to its lower side effects. Numerous medicinal plants are using by the healers and traditional physicians to control the disease conditions. Tinospora cordifolia (Willd.) Miers (Menispermaceae Family) is distinguished as Heart-Leaved Moonseed herb of the Siddha Medicine which is practicing by Tamil speaking people in Sri Lanka. This present study emphases the detailed review of the pharmacological activities of the Tinospora cordifolia (T. cordifolia) based on the previous scientific studies and textbooks. Data were collected from all existing sources such as ancient and current indigenous text books, websites, proceedings, research and review articles and other related documents based on prepared data entry form. According to this study, T. cordifolia is an important traditional plant which has a variety of pharmacological activities and medicinal usage due to the numerous chemical constituents are present in the various part of this plant. As such, this review paper can serve as evidence for researchers to conduct future scientific research as well as clinical studies in Siddha Medicine.